447 Modulation of Patient Reported Outcomes and Opioid Consumption Following Open Craniotomy: The Efficacy and Safety of Subcutaneous Sumatriptan. (April 2023) - Woodward, Josha; Kelly, Ryan Matthew; Patiel, Aahaska; Herbst, Julia; Meza, Samuel; Koro, Lacin; Keegan, Kevin; Panos, Nicholas; Munich, Stephan; Munoz, Lorenzo; Sani, Sepehr
Abstract : INTRODUCTION: Traditional pain management regimens following open craniotomy commonly employ opioid medications. As a medication class, opioids present a considerable adverse effect profile and the potential for medication abuse. Alternative medication regimens to better address post-craniotomy pain while mitigating opioid-related adverse effects are insufficiently studied. However, as a dural-based 5-HT1D receptor agonist that regulates vasoconstriction and inflammatory peptide signaling, sumatriptan shows promise to improve pain scores and reduce opioid requirements. METHODS: This is a single academic center, retrospective cohort study of 130 consecutive adult patients undergoing open craniotomy between 7/2015 and 8/2021. Patients were divided between a Control and Sumatriptan cohort contingent upon administration of a single 6mg subcutaneous injection of sumatriptan within 1-hour of surgery completion and prior to opioid administration. Opioid consumption at 6, 12 and 24-hours postoperative and admission total, inpatient length of stay (LOS) and 30-day global representation/readmission were evaluated. RESULTS: 130 patients were equally divided between the Sumatriptan and Control cohorts for analysis. No difference in baseline demographics was noted. A significant reduction of mean pain score at 6, 12 and 24-hours following surgery substantially favored the Sumatriptan cohort (p < 0.05). Further, a nonsignificant reduction in opioid requirements was observed at all timepoints favoring the sumatriptan cohort (p > 0.05). 30-day global ED evaluation and readmission rates between cohorts were similar (p > 0.05). Overall LOS in the Sumatriptan and Control cohorts were 5.3 ± 3.6 vs 6.5 ± 5.6 days (p > 0.05). No difference in the rate of incisional or intracerebral hemorrhage was noted between cohorts (p > 0.05). CONCLUSIONS: In the present study, patients in the Sumatriptan cohort demonstrated enhanced pain control and reduced opioid requirements suggesting sumatriptan represents a safe and efficacious agent for the modulation of pain following open craniotomy.